The labyrinth unfolds: architectural rearrangements of the endolysosomal system in antigen-presenting cells. (June 2019) - Perrin, Priscillia; Jongsma, Marlieke LM; Neefjes, Jacques; Berlin, Ilana
Highlights: Antigen processing for MHC-II relies on endosomal vesicle positioning and maturation. Both the internal and global endosomal architecture can be reshaped upon immune cell activation. Bidirectional endosomal movements drive MHC-II export to the cell surface. Autophagy delivers self-antigens into the endosomal pathway and can lead to autoimmunity. Abstract : Antigen-presenting cells (APCs) capture and present pathogens to T cells, thus arousing adaptive immune responses geared at the elimination of these invaders. In APCs, pathogens acquired from the extracellular space intersect with MHC class II (MHC-II) molecules in the endolysosomal system, where processing and loading of antigenic peptides occur. The resulting complexes can then be directed to the cell surface for recognition by T cells. To achieve this, the endosomal pathway of APCs must undergo dramatic rearrangements upon pathogen encounter. In this review we discuss recent strides in our understanding of how APCs modulate the organization and function of their endolysosomes to best suit different stages of antigen acquisition, processing and presentation cascade.